Genetic predictors of antidepressant side effects: A grouped candidate gene approach in the Genome-Based Therapeutic Drugs for Depression (GENDEP) study. (February 2014) - Hodgson, Karen; Uher, Rudolf; Crawford, Andrew A; Lewis, Glyn; O'Donovan, Michael C; Keers, Robert; Dernovšek, Mojca Z; Mors, Ole; Hauser, Joanna; Souery, Daniel; Maier, Wolfgang; Henigsberg, Neven; et al.
Background: The unwanted side effects associated with antidepressants are key determinants of treatment adherence in depression; propensity to experience these adverse drug reactions (ADRs) may be influenced by genetic variation. However, previous work attempting to ascertain the genetic variants involved has had limited success, in part due to the range of ADRs reported with antidepressants. Method: ADRs reported with antidepressant treatment were categorised using their likely pharmacological basis; adrenergic, cholinergic, serotonergic and histaminergic. To identify genetic predictors of susceptibility to each group of ADRs, a candidate gene analysis was performed with data from 431 depressed patients (from a total sample size of 811 patients) enrolled in the Genome-Based Therapeutic Drugs for Depression (GENDEP) project, who were randomly allocated to receive treatment with escitalopram or nortriptyline. Data from 474 patients treated with citalopram or reboxetine in the GenPod project (total sample of 601 patients) were used for replication of significant findings. Results: We found no significant predictors of presumed adrenergic, cholinergic and histaminergic ADRs. Putative serotonergic ADRs were significantly associated with variation in the gene encoding the serotonin 2C receptor ( HTR2C, rs6644093, odds ratio (OR)=1.72, 95% confidence interval (CI)=1.31−2.25, p= 7.43×10 −5 ) in GENDEP. However, this finding was not replicated in GenPod. Conclusions: The association between serotonergic side effects and variation in the HTR2C gene in the GENDEP sample supports the hypothesis that serotonin receptor-mediated mechanisms underlie these adverse reactions, however this finding was not replicated in GenPod.